Credibility Increases Visit Intention, but Misinformation Risk Weakens It: Evidence from TikTok F&B Search - Agung Stefanus Kembau; Grace Felicia Djayapranata; Antonius Felix; Ali Wardhana; Fresi Breatrix Lendo (Master of Management, School of Business and Management, Petra Christian University, 2026)
TikTok increasingly serves as an experiential search environment for Indonesian Gen-Z, shaping how food and beverage (F&B) venues are discovered, evaluated, and chosen. This study investigates how perceived affordances and perceived search value influence perceived credibility in TikTok-based F&B search, how credibility and search satisfaction subsequently shape visit intention, and under what conditions perceived misinformation risk weakens this process. A cross-sectional survey of Gen-Z TikTok users in Greater Jakarta (N = 234) was analyzed using partial least squares structural equation modeling. The results indicate that both perceived affordances and perceived search value enhance perceived credibility, with search value emerging as the relatively stronger route. Credibility increases search satisfaction, and together credibility and satisfaction are associated with higher intention to visit F&B venues found via TikTok. The findings also show that when users perceive higher misinformation risk on the platform, the positive relationship between credibility and visit intention becomes weaker, indicating that trust in content does not automatically translate into action under conditions of platform-level skepticism. The study contributes an integrated mechanism that links platform design and experiential value to credibility, satisfaction, and behavioral intention, while identifying perceived misinformation risk as a boundary condition for conversion. For managers, the findings highlight the importance of designing high-fit, low-friction discovery experiences and strengthening transparent integrity signals so that short-video search more reliably leads to offline visits.